Algorithmic management: The case of Airbnb. (October 2019) - Cheng, Mingming; Foley, Carmel
Highlights: Asymmetry of algorithmic information can increase Airbnb's power to influence and control Airbnb hosts' practices. Airbnb hosts develop their "algorithmic competency". Concern as to how the sharing economy platforms can raise their accountability. Abstract: Algorithmic management is rapidly emerging as a strategic management tool in the digital economy; however, little is known of the outcomes of algorithmic management for users of the sharing economy platforms. With a focus on one of the most rapidly growing peer-to-peer platforms, this research investigates how Airbnb hosts have responded to and adapted to the algorithmic management strategies employed by Airbnb. Findings suggest that asymmetry of algorithmic information can increase Airbnb's power to influence and control Airbnb hosts' practices. Further, such information asymmetry can significantly hinder Airbnb hosts' sense of control. This study contributes to the emerging academic dialogue on the algorithmic management in tourism and hospitality and advances the academic research on the human resources aspect of the sharing economy.